Capacidad biocontroladora del hongo trichoderma spp. hacia alternaria spp. en elcultivo de brócoli (brassicae olaracea) - Chávez Arteaga, Karen Tatiana (2022)
The excessive use of fungicides to control Alternaria spp., caused this pathogen to acquire resistance. Biological controllers in agriculture offer an alternative in reducing the use of agrochemicals and helping in the physiological aspects of plants. The objective was to evaluate the antagonistic capacity of native Trichoderma strains towards the pathogenic fungus Alternaria spp. A set of eight Trichoderma strains isolated from the Cotopaxi area and identified at the molecular level with ITS 1 and ITS4 were analyzed and they were analyzed for the detection of the ech42 gene.